Analysis of Green Purchase Intention in Coffee Shops and Restaurants: An Empirical Analysis (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
Customers are now familiar with terms such as ozone-friendly, eco-friendly, recycled materials and green products. Due to the perception of high value that costumers associate with the concept of green, green marketing strategy and green supply chain management trends have developed among companies that want to remain competitive in their respective businesses. Likewise, in terms of the café and restaurant business, it has grown significantly over the past decade, but is currently facing another challenge in meeting the modern need for products that fit the requirements of the new eco-friendly concept. In this study, researchers want to know what variables affect Green Purchase Intention in Coffee Shops and Restaurants in Bandung City. The results of this study found that Green Supply Chain Management affects the main determinant of this research to encourage the increase of Green Purchase Intention.